Greater Trochanteric Pain Syndrome: Percutaneous Tendon Fenestration Versus Platelet‐Rich Plasma Injection for Treatment of Gluteal Tendinosis. (23rd September 2016) - Jacobson, Jon A.; Yablon, Corrie M.; Henning, P. Troy; Kazmers, Irene S.; Urquhart, Andrew; Hallstrom, Brian; Bedi, Asheesh; Parameswaran, Aishwarya
Abstract : Objectives: The purpose of this study was to compare ultrasound‐guided percutaneous tendon fenestration to platelet‐rich plasma (PRP) injection for treatment of greater trochanteric pain syndrome. Methods: After Institutional Review Board approval was obtained, patients with symptoms of greater trochanteric pain syndrome and ultrasound findings of gluteal tendinosis or a partial tear (<50% depth) were blinded and treated with ultrasound‐guided fenestration or autologous PRP injection of the abnormal tendon. Pain scores were recorded at baseline, week 1, and week 2 after treatment. Retrospective clinic record review assessed patient symptoms. Results: The study group consisted of 30 patients (24 female), of whom 50% were treated with fenestration and 50% were treated with PRP. The gluteus medius was treated in 73% and 67% in the fenestration and PRP groups, respectively. Tendinosis was present in all patients. In the fenestration group, mean pain scores were 32.4 at baseline, 16.8 at time point 1, and 15.2 at time point 2. In the PRP group, mean pain scores were 31.4 at baseline, 25.5 at time point 1, and 19.4 at time point 2. Retrospective follow‐up showed significant pain score improvement from baseline to time points 1 and 2 ( P < .0001) but no difference between treatment groups ( P = .1623). There was 71% and 79% improvement at 92 days (mean) in the fenestration and PRP groups, respectively, with no significant difference between the treatments ( P >.99). Conclusions: Our study shows that both ultrasound‐guided tendon fenestration and PRP injection are effective for treatment of gluteal tendinosis, showing symptom improvement in both treatment groups.